ANALYSIS OF CAPACITY MANAGEMENT IN ADDRESSING PRODUCTION OVERLOAD IN A SNACK FOOD COMPANY - Dimas Septiandy; Nur Ahmadi Bi Rahmani; Faisal Umardani Hasibuan (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aimed to analyse production capacity management in a snack food company in dealing with production overload, particularly during high-demand periods such as Christmas, New Year, and Eid. This research used a descriptive qualitative approach with semi-structured interviews consisting of ten questions addressed to employees in the production, operations, and warehouse departments. The questions covered capacity adjustment strategies, overtime policies, recruitment of additional workers, raw material management, production constraints, quality supervision, post-production evaluation, assessment of current capacity, scheduling of production and distribution, and technology investment. In addition to interviews, direct observation was conducted to ensure the consistency between employees’ statements and the actual field conditions. The results show that the company relies on historical data-based planning, workforce optimisation, and production flexibility to handle increased demand. However, challenges such as product quality, limited machinery, and time pressure remain major issues that require continuous management. These findings provide a comprehensive overview of the importance of adaptive capacity strategies in the snack food industry.